Nanometer silicon-based negative electrode material and preparation method and application thereof
By loading ZIF-8 on the silicon surface and forming a highly conductive CN matrix material during the carbonization process, the problems of poor structural uniformity and weak interface bonding in the preparation of silicon carbon negative electrode materials are solved, and the conductivity and cyclic stability of the electrode are significantly improved.
Patent Information
- Application Number
- CN202411871377.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
The preparation of existing silicon carbon negative electrode materials has problems such as poor structural uniformity, insufficient pore structure optimization, high cost and complexity, and weak interface combination, which has led to the failure to effectively solve the problem of volume expansion and insufficient conductivity of silicon negative electrode materials.
By loading the Zeolitic Imidazolate Framework-8 (ZIF-8) on the silicon surface, a high specific surface area and multi-stage pore distribution are retained after carbonization, forming a dense and uniform core-shell structure, improving the interface stability between silicon and carbon, and generating a highly conductive CN matrix material through high-temperature sintering.
It significantly improves the electron conduction performance of the electrode, improves the specific capacity and cyclic stability of the material, solves the problems of volume expansion and insufficient conductivity, and provides a new idea for large-scale preparation of high specific capacity and high stability silicon carbon negative electrode materials.
Smart Images

Figure CN119674012A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a nano silicon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] As an important form of contemporary energy storage, the performance of lithium-ion batteries is directly related to the development of electric vehicles, portable electronic devices, energy storage systems and other fields. Silicon-based negative electrode materials have a theoretical specific capacity of up to 3579mAh / g, showing great potential compared to traditional graphite negative electrode materials, and have become a hot spot in current lithium-ion battery research. However, silicon-based negative electrode materials face a series of challenges in practical applications, especially silicon will produce a volume expansion of more than 300% during the lithium insertion / delithiation process. This characteristic leads to the pulverization of electrode materials, the destruction of the conductive network and the instability of the solid electrolyte interface (SEI) film, which seriously affects the cycle life and electrochemical performance of the battery.
[0003] In order to solve the volume expansion problem of silicon anode, researchers have proposed a variety of preparation methods for silicon-carbon composite materials, aiming to improve the structural stability and conductivity of silicon anode by introducing carbon materials. Existing technical methods mainly include mechanical ball milling, chemical vapor deposition (CVD), sol-gel, hydrothermal and microwave methods, template method and spray drying.
[0004] The mechanical ball milling method combines silicon particles with a carbon source by physical mixing and grinding. Although the process is simple and the cost is low, it has disadvantages such as poor material consistency and difficult to control particle size, resulting in limited performance improvement in high-performance battery applications. The CVD method can form a dense and uniform carbon layer coating on the surface of silicon particles, significantly improving the conductivity and interface stability of the material, but the high equipment cost and complex process limit its large-scale industrial application. Although the sol-gel method, hydrothermal method and microwave method can prepare silicon-carbon composite materials with uniform structure and nanoscale dispersion, they have high requirements for equipment and complex process parameter control, which is also not conducive to large-scale production. The template rule can accurately control the pore structure and size of the composite material, but the preparation and removal process of the template is complicated and costly, which also limits its wide application. Although the spray drying method has a simple preparation process and is suitable for mass production, the specific surface area of the prepared material is low, which affects the rate performance of the battery.
[0005] In summary, although the existing preparation methods of silicon-carbon negative electrode materials have their own characteristics, they generally have problems such as poor structural uniformity, insufficient pore structure optimization, high cost and complexity, and weak interface bonding. As a result, the volume expansion and insufficient conductivity of silicon negative electrode materials have not been effectively solved, resulting in poor morphology uniformity, uneven coating, low gram-to-weight ratio, insufficient cycle performance, poor composition controllability and energy efficiency of the obtained silicon-carbon negative electrode materials. Summary of the invention
[0006] The technical problem to be solved by the present invention is that the preparation of existing silicon-carbon negative electrode materials has problems such as poor structural uniformity, insufficient pore structure optimization, high cost and complexity, and weak interface bonding, resulting in the volume expansion and insufficient conductivity problems of silicon negative electrode materials not being effectively solved. The purpose of the present invention is to provide a nano-silicon-based negative electrode material and its preparation method and application, which solves the problems of poor structural uniformity, insufficient pore structure optimization, high cost and complexity, and weak interface bonding.
[0007] The present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a nano-silicon-based negative electrode material, comprising the following steps:
[0009] Surface modification of nano-silicon: Silicon nanoparticles, surface modifiers and solvents are uniformly mixed to obtain a surface modification reaction suspension of nano-silicon. After stirring for reaction, the bottom precipitate is separated by centrifugation and dried to obtain surface-modified nano-silicon.
[0010] In-situ growth of ZIF-8 on nano-silicon surface: the surface-modified nano-silicon is dispersed in a methanol solution, zinc nitrate and 2-methylimidazole are added, and a uniform suspension is obtained after the zinc nitrate and 2-methylimidazole are dissolved. After stirring for reaction, the bottom precipitate is separated by centrifugation, and the precipitate is washed and dried to obtain a composite material powder;
[0011] Carbonization treatment: The composite material powder is sintered in a reducing atmosphere to obtain a nano-silicon-based negative electrode material.
[0012] As a possible design, the average particle size of the nano-silicon is 15nm-100nm.
[0013] As a possible design, the surface modifier includes one of sodium polystyrene sulfonate, polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide, and the solvent includes one of methanol, ethanol and isopropanol.
[0014] As a possible design, the concentration of nano-silicon in the above methanol solution is 10-50 g / L.
[0015] As a possible design, the molar concentration of the zinc nitrate is 5-100 mM, and the molar ratio of zinc nitrate to 2-methylimidazole is 1:(4-20).
[0016] As a possible design, the reducing atmosphere comprises an inert mixed gas with a volume concentration of 5-20%.
[0017] As a possible design, the above sintering is specifically to first introduce a reducing atmosphere for 30-60 minutes, and then sinter at a constant temperature of 600-900°C for 1-8 hours.
[0018] As a possible design, the sintering temperature is specifically raised to 600-900° C. at a rate of 2-10° C. / min.
[0019] In a second aspect, the present invention provides a nano silicon-based negative electrode material prepared by the above-mentioned preparation method.
[0020] In a third aspect, the present invention provides an application of a nano silicon-based negative electrode material prepared by the above preparation method in the preparation of a lithium ion battery.
[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0022] The present invention loads Zeolitic Imidazolate Framework-8 (ZIF-8, zeolite imidazolate framework) on the silicon surface. ZIF-8 is a metal organic framework (MOF) material. The skeleton structure of ZIF-8 can be used in the preparation of negative electrode materials. After carbonization, a high specific surface area and multi-level pore distribution are retained, which is conducive to the rapid transmission of lithium ions and the buffering of volume expansion; with the help of the porous carbon material derived from it, a dense and uniform core-shell structure can be formed on the surface of silicon particles, improving the interface stability between silicon and carbon; after carbonization, the conductivity can be improved, and the electronic conductivity of the electrode can be significantly improved; in addition, the imidazole ligand contained in ZIF-8 can introduce nitrogen doping during the carbonization process, further improving the conductivity and active sites of the carbon material, and helping to improve the specific capacity and cycle stability of the material. Finally, it is reflected in the material that the structural stability and electrochemical performance of the material can be improved, the volume expansion problem of silicon-based negative electrode materials can be improved, the irreversible capacity loss can be reduced, and a new idea is provided for the large-scale preparation of high-specific capacity and high-stability silicon-carbon negative electrode materials.
[0023] The invention enhances the binding force between ZIF-8 and nano-silicon by modifying the surface of nano-silicon, so that the nano-silicon is evenly distributed; realizes the uniform encapsulation of high-load nano-silicon by ZIF-8 through in-situ growth; converts the organic ligand in ZIF-8 into a highly conductive CN matrix material through sintering, and forms a strong binding force with the surface of nano-silicon; at the same time, the sublimation of Zn and the overflow of small molecule gas during the calcination process will form a porous structure with high porosity, and the formed core-shell structure and uniform high-crystalline carbon coating improve the cycle stability and comprehensive conductive performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0025] Figure 1 is a flow chart of the preparation method of the present invention;
[0026] Figure 2 It is a schematic diagram of the microstructure of the composite material powder and the nano-silicon-based negative electrode material of the present invention. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0028] Due to the poor structural uniformity, insufficient pore structure optimization, high cost and complexity, and weak interface bonding in the preparation of existing silicon-carbon negative electrode materials, the volume expansion and insufficient conductivity problems of silicon negative electrode materials have not been effectively solved.
[0029] The present invention provides a method for preparing a nano silicon-based negative electrode material, wherein the surface of nano silicon is modified to improve the subsequent binding force with ZIF-8, so that ZIF-8 is evenly distributed on the surface of nano silicon; and by loading ZIF-8, the advantages of nano silicon and ZIF-8 are combined to improve the specific surface area and multi-level pore distribution of the material, so that the porous carbon material derived from ZIF-8 can form a dense and uniform core-shell structure on the surface of silicon particles, improve the interface stability between silicon and carbon, and improve the conductivity, specific capacity and cycle stability; finally, by high-temperature sintering, the nano silicon @ ZIF-8 is carbonized, the organic ligand in ZIF-8 is converted into a highly conductive CN matrix material, and a strong binding force is formed with the surface of nano silicon, and the sublimation of Zn and the overflow of small molecule gas during the calcination process will form a porous structure with high porosity. Finally, a nano silicon-based negative electrode material with good morphology uniformity, uniform coating, high gram specific capacity, good cycle performance, high component controllability and low energy efficiency is obtained.
[0030] A method for preparing a nano silicon-based negative electrode material, referring to Figure 1 , including the following steps:
[0031] S1. Surface modification of nano-silicon (p-Si NPs): Silicon nanoparticles, a surface modifier and a solvent are uniformly mixed to obtain a surface modification reaction suspension of nano-silicon. After stirring for reaction, the bottom precipitate is separated by centrifugation and dried to obtain surface-modified nano-silicon (p-Si NPs).
[0032] By modifying the surface of nano-silicon, the subsequent binding force between ZIF-8 and nano-silicon and the uniform distribution of nano-silicon are enhanced, which facilitates the subsequent ZIF-8 loading.
[0033] In some embodiments of the present invention, the average particle size of the nano-silicon is 15 nm-100 nm. The average particle size can be any value within the range of 15 nm-100 nm, such as 30 nm, 50 nm and 80 nm.
[0034] In some embodiments of the present invention, the surface modifier includes one of sodium polystyrene sulfonate (PSS), polyvinyl pyrrolidone (PVP) and cetyltrimethylammonium bromide (CTAB), and the solvent includes one of methanol, ethanol and isopropanol.
[0035] Preferably, the mass ratio of the nano-silicon particles to the surface modifier is 1:(1-5), and the concentration of the surface modifier is 10-50 g / L.
[0036] Preferably, the stirring reaction is to stir the nano-silicon surface modification reaction suspension at a speed of 100-800 rpm / min and a temperature of 30-80° C. for 6-24 hours. Preferably, the stirring can be performed in a constant temperature water bath magnetic stirrer.
[0037] Preferably, the above centrifugal separation is specifically to centrifuge the surface modification reaction suspension reaction product at a speed of 3000-8000 rpm / min for 1-10 min, and the separated precipitate is dried at 40-80° C. for 4-12 h.
[0038] S2. In situ growth of ZIF-8 on nano-silicon surface (p-Si NPs@ZIF-8): The surface-modified nano-silicon was dispersed in a methanol solution, and zinc nitrate and 2-methylimidazole were added. After the zinc nitrate and 2-methylimidazole were dissolved, a uniform suspension was obtained. After stirring for reaction, the bottom precipitate was separated by centrifugation. The precipitate was washed and dried to obtain a composite material powder (p-Si NPs@ZIF-8, refer to Figure 2 ).
[0039] By growing ZIF-8 in situ on the surface of surface-modified nano-silicon, uniform and high-density coating of nano-silicon by ZIF-8 is achieved. The resulting composite material powder can react at close to room temperature, with low energy consumption (below 60°C), and the morphology and composition of the material are highly controllable. The uniform and high-density coating of nano-silicon by ZIF-8 makes the nano-silicon evenly dispersed in the final carbon matrix and effectively prevents the agglomeration of nano-silicon.
[0040] In some embodiments of the present invention, the nano-silicon concentration in the methanol solution is 10-50 g / L. The nano-silicon concentration can be any value within 10-50 g / L, including but not limited to 30 g / L, 45 g / L and 25 g / L.
[0041] By controlling the mass concentration of the nano-silicon methanol suspension, different silicon loadings in the ZIF can be achieved, and the silicon content in the final silicon-carbon material can be controlled.
[0042] Preferably, the above dispersion is ultrasonic dispersion, and the ultrasonic dispersion conditions are at a power of 100-400W and a dispersion treatment time of 30-80min.
[0043] In some embodiments of the present invention, the molar concentration of the zinc nitrate is 5-100 mM, and the molar ratio of zinc nitrate to 2-methylimidazole is 1:(4-20).
[0044] By reacting at this ratio, the particle size of the obtained composite material powder can be controlled to be 1-5 μm.
[0045] Preferably, the stirring reaction of the uniform suspension is carried out at a constant temperature of 25-80° C. for 4-48 hours.
[0046] Preferably, the centrifugation time is 1-10 min, and after centrifugation, the product is washed with a detergent and then dried at 40-80° C. for 4-12 h.
[0047] Preferably, the detergent is methanol or ethanol.
[0048] S3. Carbonization treatment of composite powder (p-Si NPs@ZIF-8): The composite powder is sintered in a reducing atmosphere to obtain a nano-silicon-based negative electrode material (p-Si NPs@CN, refer to Figure 2 ).
[0049] High-temperature sintering of the composite material powder can achieve Zn removal and high crystallinity of the carbon coating layer, and generate a rich porous structure, enhancing the conductivity, gram-specific capacity and cycle stability of the material. The inventors have found that if the material is not sintered at a high temperature of 600-900°C, Zn will not sublimate, and the final material will contain a large amount of Zn metal element, and the porosity will be very low, and finally its porosity, electrical properties and cycle stability are very poor.
[0050] The voids generated by ZIF-8 itself during the pyrolysis process and the pore-forming effect of Zn sublimation realize a porous structure with high porosity in the powder phase of the composite material, which effectively accommodates the cyclic volume expansion of nanosilicon. The nanoscale size of nanosilicon makes its surface stress low, and it will not break or lose during the expansion process, thereby improving the cycle life.
[0051] Preferably, the sintering is carried out in a carbonization furnace.
[0052] In some embodiments of the present invention, the reducing atmosphere comprises an inert mixed gas with a volume concentration of 5-20%.
[0053] Preferably, the inert mixed gas includes a mixed gas of hydrogen and nitrogen or a mixed gas of hydrogen and argon.
[0054] In some embodiments of the present invention, the sintering is specifically to first introduce a reducing atmosphere for 30-60 minutes, and then sinter at a constant temperature of 600-900°C for 1-8 hours. The sintering temperature can be any value within 600-900°C, preferably 700-800°C, and can be 750°C, 850°C or other values.
[0055] In some embodiments of the present invention, the sintering is specifically performed by heating the temperature to 600-900° C. at a rate of 2-10° C. / min.
[0056] The present invention provides a nano silicon-based negative electrode material, which is prepared by the above-mentioned preparation method.
[0057] The present invention also provides the use of a nano silicon-based negative electrode material prepared by the above preparation method in the preparation of a lithium ion battery.
[0058] Example 1
[0059] S1. Surface modification of nano-silicon (p-Si NPs)
[0060] According to the required raw material ratio, 2g of silicon nanoparticles with an average particle size of 20nm, 4g of sodium polystyrene sulfonate (PSS), and 100mL of ethanol are uniformly mixed to obtain a surface-modified reaction suspension of nano-silicon; the above reaction suspension is stirred in a constant temperature water bath magnetic stirrer for 12h, the stirring speed is 300rpm / min, and the water bath temperature is 50°C; after the reaction is completed, centrifugation is collected and thoroughly dried in a vacuum drying oven to obtain surface-modified nano-silicon (p-Si NPs), the centrifuge speed is 4000rpm / min, the centrifugation time is 2min, the drying temperature is 60°C, and the drying time is 12h.
[0061] S2. In situ growth of ZIF-8 on nano-silicon surface (p-Si NPs@ZIF-8)
[0062] The surface-modified nano-silicon (p-Si NPs) was dispersed in a methanol solution in an ultrasonic disperser, the ultrasonic dispersion power was 400 W, the dispersion time was 60 min, and the concentration of p-Si NPs was 40 g / L; a certain proportion of zinc nitrate and 2-methylimidazole were added to the methanol solution, and the zinc nitrate and 2-methylimidazole were completely dissolved by ultrasound to form a uniform suspension, the molar ratio of zinc nitrate to 2-methylimidazole was 1:8, and the molar concentration of zinc nitrate was 20 mM; the reaction was carried out in a constant temperature water bath magnetic stirring pot for 4 to 48 hours, and the water bath temperature was 50°C; after the reaction was completed, the composite material powder (p-Si NPs@ZIF-8) was obtained by centrifugation, washing, and vacuum drying, the centrifuge speed was 6000 rpm / min, the centrifugation time was 5 min, the detergent was methanol, the drying temperature of the vacuum oven was 60°C, and the drying time was 12 h.
[0063] S3, Carbonization treatment of p-Si NPs@ZIF-8
[0064] The composite material powder (p-Si NPs@ZIF-8) was placed in a carbonization furnace, introduced into a reducing atmosphere, and sintered to obtain a finished material; wherein the added mass of p-Si NPs@ZIF-8 was 2 g, and the reducing atmosphere was a 10% hydrogen / argon mixture. The reducing atmosphere was introduced for 0.5 h before carbonization, and the carbonization furnace was heated to 800 ° C at a rate of 5 ° C / min, and the sintering time was 2 h. The prepared product was recorded as p-Si NPs@CN, in which the mass proportion of Si was 81%.
[0065] Example 2
[0066] This embodiment is substantially the same as embodiment 1, except that in step S2, the concentration of p-Si NPs is 10 g / L, the molar ratio of zinc nitrate to 2-methylimidazole is 1:8, and the molar concentration of zinc nitrate is 20 mM.
[0067] The mass proportion of nano-Si in the final porous silicon-carbon negative electrode material obtained is about 43%, and the sample is marked as: p-Si NPs@CN-1.
[0068] Example 3
[0069] This embodiment is basically the same as Embodiment 1, except that: the concentration of p-Si NPs in step S2 is adjusted to 20 g / L, the molar ratio of zinc nitrate and 2-methylimidazole is 1:8, wherein the molar concentration of zinc nitrate is 20 mM, and the nano-silicon content in the final porous silicon-carbon negative electrode material is approximately 52%. The sample is labeled: p-Si NPs@CN-2.
[0070] Example 4
[0071] This embodiment is substantially the same as embodiment 1, except that: the concentration of p-Si NPs in step S2 is adjusted to 30 g / L, the molar ratio of zinc nitrate to 2-methylimidazole is 1:8, and the molar concentration of zinc nitrate is 20 mM.
[0072] The final porous silicon-carbon negative electrode material contains about 71% nano-silicon, and the sample is labeled as: p-Si NPs@CN-3.
[0073] Example 5
[0074] This embodiment is substantially the same as Embodiment 1, except that: the concentration of p-Si NPs in step S22 is adjusted to 50 g / L, the molar ratio of zinc nitrate to 2-methylimidazole is 1:8, and the molar concentration of zinc nitrate is 20 mM.
[0075] The final porous silicon-carbon negative electrode material contains about 92% nano-silicon, and the sample is labeled as: p-Si NPs@CN-5.
[0076] Comparative Example 1
[0077] This comparative example is basically the same as Example 1, except that step S1 is omitted, and Si NPs without surface modification are directly used for in-situ growth and carbonization treatment. The sample is marked as Si NPs / CN-1.
[0078] Comparative Example 2
[0079] This comparative example is basically the same as Example 1, except that ZIF-8 is replaced by MOF-5, and step S2-3 is adjusted accordingly, as follows.
[0080] S2. In situ growth of MOF-5 on nano-silicon surface (p-Si NPs@MOF-5)
[0081] First, prepare solution A: dissolve zinc salt (such as Zn(NO3)2·6H2O) in 100mL solvent (such as DMF or methanol) at a concentration of 50mM. Dissolve terephthalic acid (H2BDC) in another 100mL solvent at a concentration of 50mM and stir until completely dissolved to form solution B. Then disperse p-Si NPs in solution A and ultrasonically disperse for 40 minutes (power 300W) to form a uniform dispersion with a nano-silicon concentration of 40g / L. Under magnetic stirring, slowly add solution B to solution A, keeping the molar ratio (zinc salt: H2BDC) at 1:3. React in a constant temperature water bath for 12 hours at a temperature of 120°C, with continuous stirring during the reaction.
[0082] After the reaction, the reaction mixture was centrifuged (6000 rpm, 5 minutes) to collect the precipitate. It was washed with deionized water and ethanol three times to remove the solvent and unreacted raw materials and by-products. The product was dried in a vacuum drying oven at 80 ° C for 12 hours to obtain a p-Si NPs@MOF-5 composite material.
[0083] S3, Carbonization treatment of p-Si NPs@MOF-5
[0084] The composite material powder (p-Si NPs@MOF-5) was placed in a carbonization furnace, introduced into a reducing atmosphere, and sintered to obtain a finished material; wherein the added mass of p-Si NPs@ZIF-8 was 2 g, and the reducing atmosphere was a 10% hydrogen / argon mixture. The reducing atmosphere was introduced for 0.5 h before carbonization, and the carbonization furnace was heated to 800 ° C at a rate of 5 ° C / min, and the sintering time was 2 h. The prepared product was recorded as p-Si NPs@Zn / C.
[0085] Performance verification of p-Si NPs@Zn / C anode material
[0086] The p-Si NPs@Zn / C negative electrode material was mixed with PVDF and Super P in a mass ratio of 8:1:1 to form a slurry, which was coated on the copper foil current collector and finally made into a CR2032 button battery for testing. The test voltage window was 0-3V.
[0087] Comparative Example 3
[0088] This comparative example is substantially the same as Example 1, except that the molar concentration of zinc nitrate in step S2 is 2 mM.
[0089] Comparative Example 4
[0090] This comparative example is substantially the same as Example 1, except that the molar concentration of zinc nitrate in step S2 is such that the molar ratio of zinc nitrate to 2-methylimidazole is 1:25.
[0091] Comparative Example 5
[0092] This comparative example is substantially the same as Example 1, except that the concentration of p-Si NPs in step S2 is 5 g / L.
[0093] Comparative Example 6
[0094] This comparative example is basically the same as Example 1, except that the sintering temperature in step S3 is 500°C.
[0095] Experimental Example 1
[0096] The performance of Examples 1-5, Comparative Examples 1-2 and 81% Si NPs were verified to obtain electrochemical performance test results, including the first reversible specific capacity, the first charge and discharge efficiency, the 200 cycle reversible specific capacity and the 200 cycle capacity retention rate.
[0097] The negative electrode material or Si NPs was mixed with PVDF and Super P in a mass ratio of 8:1:1 to form a slurry, which was then coated on a copper foil current collector and finally made into a CR2032 button cell for testing, with a test voltage window of 0-3V.
[0098] The electrochemical performance test results are shown in Table 1.
[0099] Table 1 Electrochemical performance test results
[0100]
[0101] Observing Table 1, it can be seen that Example 1 has the best comprehensive electrochemical performance. This is because it has a suitable nano-Si loading amount, and the Si NPs are highly dispersedly coated with a high-porosity carbon-nitrogen matrix, which improves the conductivity and promotes the formation of a good SEI, so it has an extremely high first reversible specific capacity and first charge and discharge efficiency. The nanoscale silicon particles and the porous structure with high porosity ensure the stability of nano-silicon during the charge and discharge process. Therefore, the capacity retention rate after 200 cycles is as high as 87% or more. Comparing Example 1 with Comparative Example 1, the reversible specific capacity and 200 cycle performance of Comparative Example 1 are both poor. This is because the lack of surface modification leads to insufficient pore-forming ability, resulting in poor performance. Comparing Example 1 with Comparative Example 2, the reversible specific capacity of Comparative Example 2 is poor, which shows that not all skeleton materials can be used as raw materials. Only ZIF-8 can make the prepared negative electrode material have the best comprehensive performance. Comparing Example 1 with Comparative Example 3, it can be seen that the reversible specific capacity after 200 cycles and the capacity retention rate after 200 cycles are significantly reduced. This is because the Zn concentration is too low and a large number of silicon particles cannot be effectively encapsulated by ZIF, so it has a higher specific capacity but poorer cycle efficiency. Comparing Example 1 with Comparative Example 4, the 200 cycle performance of Comparative Example 4 is poor. This is because the Zn: dimethylimidazole ratio is high, the ZIF particles produced are smaller, and the pores in the silicon-carbon negative electrode produced are lower, and the stability during the cycle is lower. Comparing Example 1 with Comparative Example 5, the reversible specific capacity of Comparative Example 5 is significantly reduced. This is because the concentration of Si nanoparticles in this comparative example is too low and the silicon load in ZIF is low, so its capacity is greatly reduced, but the long-cycle stability is better. Comparing Example 1 and Comparative Example 6, the 200 cycle performance and 200 cycles of Comparative Example 6 are both very poor. This is because 500 degrees Celsius is not enough for the sublimation of Zn, so the Zn content in the material is extremely high, which directly leads to a decrease in gram capacity, insufficient pore-forming ability, and poor cycle stability.
[0102] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a nano-silicon-based negative electrode material, characterized in that: The steps include: Surface modification of nano-silicon: Silicon nanoparticles, surface modifiers and solvents are uniformly mixed to obtain a surface modification reaction suspension of nano-silicon. After stirring for reaction, the bottom precipitate is separated by centrifugation and dried to obtain surface-modified nano-silicon. In-situ growth of ZIF-8 on nano-silicon surface: the surface-modified nano-silicon is dispersed in a methanol solution, zinc nitrate and 2-methylimidazole are added, and a uniform suspension is obtained after the zinc nitrate and 2-methylimidazole are dissolved. After stirring for reaction, the bottom precipitate is separated by centrifugation, and the precipitate is washed and dried to obtain a composite material powder; Carbonization treatment: The composite material powder is sintered in a reducing atmosphere to obtain a nano-silicon-based negative electrode material.
2. The method for preparing a nano silicon-based negative electrode material according to claim 1, characterized in that: The average particle size of the nano silicon is 15nm-100nm.
3. The method for preparing a nano silicon-based negative electrode material according to claim 1, characterized in that: The surface modifier includes one of sodium polystyrene sulfonate, polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide, and the solvent includes one of methanol, ethanol and isopropanol.
4. The method for preparing a nano silicon-based negative electrode material according to claim 1, characterized in that: The nano-silicon concentration in the methanol solution is 10-50 g / L.
5. The method for preparing a nano silicon-based negative electrode material according to claim 1, characterized in that: The molar concentration of the zinc nitrate is 5-100 mM, and the molar ratio of zinc nitrate to 2-methylimidazole is 1:(4-20).
6. The method for preparing a nano-silicon-based negative electrode material according to claim 1, characterized in that: The reducing atmosphere includes an inert mixed gas with a volume concentration of 5-20%.
7. The method for preparing a nano silicon-based negative electrode material according to claim 1, characterized in that: The sintering is specifically to first introduce a reducing atmosphere for 30-60 minutes, and then sinter at a constant temperature of 600-900° C. for 1-8 hours.
8. The method for preparing a nano-silicon-based negative electrode material according to claim 7, characterized in that: The sintering is specifically carried out by heating the temperature to 600-900° C. at a rate of 2-10° C. / min.
9. A nano silicon-based negative electrode material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of a nano-silicon-based negative electrode material prepared by the preparation method according to any one of claims 1 to 8 in the preparation of lithium-ion batteries.
Citation Information
Patent Citations
Silicon-based negative electrode material and preparation method and application thereof
CN110729472A
Preparation method of silicon-carbon composite anode material
CN112467136A
Self-supporting nitrogen-doped porous carbon-coated silicon nanofiber material for negative electrode of lithium ion battery as well as preparation method and application of self-supporting nitrogen-doped porous carbon-coated silicon nanofiber material
CN113629251A
Bi-metal MOF-derived Si-coated CoCu-ZIF composite negative electrode material and preparation method and application thereof
CN114597358A
Preparation method of Fe-doped Si / C composite material for negative electrode of lithium ion battery
CN114883569A
Cited By
Silicon-based negative electrode sheet, preparation method thereof and solid-state battery
CN122511843A